Managerial Incentives and Internal Capital Markets - de Motta, Adolfo (Journal of Finance, 2003)
Capital budgeting in multidivisional firms depends on the external assessment of the whole firm, as well as on headquarters' assessment of the divisions. While corporate headquarters may create value by directly monitoring divisions, the external assessment of the firm is a public good for division managers who, consequently, are tempted to free ride. As the number of divisions increases, the free‐rider problem is aggravated, and internal capital markets substitute for external capital markets in the provision of managerial incentives. The analysis relates the value of diversification to characteristics of the firm, the industry, and the capital market.